Capacidade antioxidante e antimicrobiana in vitro de extratos de flores comestíveis obtidos pelo método convencional e ultrassom - Franzen, Felipe de Lima (2017)
The objective of this work was to investigate the influence of different methods of extraction (conventional and ultrasound) on the yield and contents of petal extracts of cultivated edible flowers (rose, sunflower and calendula), in order to verify the antioxidant and antimicrobial capacity. The flowers were cultivated and evaluated for the centesimal composition and caloric value of the petals. Different solvent, time and temperature were used in the extraction methods. The extracts were characterized as total phenolic content and total flavonoids. The antioxidant activity in vitro was quantified by the DPPH method, the IC50 was calculated and the antimicrobial activity was evaluated. The species presented high water content (greater than 80%), while the sunflower had higher ash content (1,2%), marigold presented higher content of ethereal extract (1,2%) and rose presented higher content of fibers (3,5%). The results showed that the highest contents of petal extracts were obtained using 120 minutes of extraction, with predominance of the rose species, independent of the method, solvent and temperature, except in the conventional extraction method in hot water where the highest extract content was in the extraction period of 30 minutes. The extract with the highest yield was extracted by the ultrasound method in hot water. Rose and sunflower petal extracts obtained higher yields. The extracts of rose petals obtained by the ultrasonic method with temperatures of 20º and 60º C presented higher contents of phenolic compounds (17,50 g EAG mL-1 and 28,99 g EAG mL-1 extract, respectively) and flavonoids (16,86 g EQ mL-1 and 20,26 g EQ mL-1 extract, respectively). The results indicate that the ethanolic extracts of rose petals have high antioxidant capacity. It was verified that the ethanolic extract of rose petals by the ultra-sonic method at a temperature of 20º C was more efficient presenting the IC50 value of 0,75 mg mL-1 of extract, antioxidant activity proved by the DPPH method. The extracts did not present antimicrobial activity, by the disk diffusion test and neither antifungal activity. In this way, flower petal extracts prove to be a viable alternative as a natural antioxidant in place of synthetic antioxidants, with possibilities of industrial applications in food products.